Health status and risk profiles for brain aging of rural‐dwelling older adults: Data from the interdisciplinary baseline assessments in MIND‐China - Yongxiang Wang; Xiaolei Han; Xianda Zhang; Zhonglin Zhang; Lin Cong; Shi Tang; Tingting Hou; Cuicui Liu; Xiaojuan Han; Qinghua Zhang; Jianli Feng; Ling Yin; et al. (Alzheimer’s & Dementia: Translational Research & Clinical Interventions)
Abstract Introduction Multidomain intervention approaches have emerged as a potential strategy to reduce dementia risk. We sought to describe the baseline assessment approaches, health conditions, and risk profiles for brain aging of participants in the randomized controlled Multimodal INterventions to delay Dementia and disability in rural China (MIND‐China). Methods MIND‐China engaged residents who were ≥60 years of age and living in rural communities in the western Shandong province. In March to September 2018, all participants underwent the core module assessments via face‐to‐face interviews, clinical examinations, neuropsychological testings, and laboratory tests. Specific modules of examination were performed for sub‐samples, including brain magnetic resonance imaging scans, genetic and blood biochemical markers, actigraphy testing, cardiopulmonary coupling analysis for sleep quality and disturbances, audiometric testing, and optical coherence tomography examination. We performed descriptive analysis. Results In total, 5765 participants (74.9% of all eligible residents) undertook the baseline assessments. The mean age was 70.9 years (standard deviation, 5.9), 57.2% were women, 40.6% were illiterate, and 88.3% were farmers. The overall prevalence of common chronic diseases was 67.2% for hypertension, 23.4% for dyslipidemia, 23.5% for heart disease, 14.4% for diabetes mellitus, and 5.4% for dementia. The prevalence rates of hypertension, diabetes mellitus, dyslipidemia, obesity, heart disease, depressive symptoms, and dementia were higher in women than in men (P < .05). Overall, 87.1% of the participants had at least two of the 15 chronic diseases (89.3% in women vs 84.2% in men, P < .001). Participants examined for the specific modules were younger, more likely to be women, and more educated than those not examined. Discussion Comprehensive baseline assessments of participants in MIND‐China provide extremely valuable data sources for interdisciplinary research into the complex relationships of aging, health, brain aging, and functional consequences among older adults living in the rural communities. Highlights MIND‐China is a multimodal intervention study among rural residents ≥60 years of age. At baseline, 5765 participants undertook the interdisciplinary assessments. The baseline assessments consisted of core module and specific modules. Specific modules included brain magnetic resonance imaging (MRI), blood biomarkers, ActiGraph, cardiopulmonary coupling (CPC), pure‐tone audiometry (PTA), and optical coherence tomography (OCT).